2020
DOI: 10.5603/nmr.a2020.0016
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT in thyroid cancer — the importance of BRAF mutations

Abstract: Thyroid cancer (TC) represents less than 1% of all newly diagnosed malignancies. In some selected cases, with a high clinical suspicion for disease but negative I-131 scan, positron emission tomography/computed tomography (PET) with F-18-Fluorodeoxyglucose (FDG) could be helpful in the detection of disease and the definition of its extent. FDG PET/CT, better if performed after TSH stimulation analogously to patient preparation done for radioiodine scintigraphy, could be useful mainly in the detection of metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Otherwise, BRAF mutation (BRAFV600E) is the most frequently observed genetic abnormality in PTC, which is capable of inducing excessive proliferation and differentiation of tumor cells in its initial stages (and is also involved in tumorigenesis and in the conversion to a more aggressive undifferentiated phenotype) [78][79][80]. Thus, individuals in whom PTC coexists with HT have been observed to be at lower risk of extrathyroidal extension of the PTC and additionally, it has been suggested that HT antagonizes PTC progression in the presence of BRAFV600E.…”
Section: Probable Molecular Mechanisms Associated Between Ht and Dtcmentioning
confidence: 99%
“…Otherwise, BRAF mutation (BRAFV600E) is the most frequently observed genetic abnormality in PTC, which is capable of inducing excessive proliferation and differentiation of tumor cells in its initial stages (and is also involved in tumorigenesis and in the conversion to a more aggressive undifferentiated phenotype) [78][79][80]. Thus, individuals in whom PTC coexists with HT have been observed to be at lower risk of extrathyroidal extension of the PTC and additionally, it has been suggested that HT antagonizes PTC progression in the presence of BRAFV600E.…”
Section: Probable Molecular Mechanisms Associated Between Ht and Dtcmentioning
confidence: 99%
“…Nuclear imaging for disease evaluation tie such as cancer and other non-malignant diseases is increasingly used to explore the disease phenotype and to support re-individualized clinical decision-making on the road to personalized medicine [ 66 ]. One of the biggest challenges promising for radiomics analysis on PET imaging in breast cancer is the prediction of Pathological Complete Response (pCR) to chemotherapy treatment neoadjuvants, as this is an important factor prognostic.…”
Section: Functional Imagingmentioning
confidence: 99%
“…18 F-FDG PET/CT is the most common molecular imaging technique for preoperative staging of various malignancies, due to the higher metabolic rate of cancerous cells compared to normal ones [ 39 , 40 , 41 , 42 ], however, as a glucose analog, 18 F-FDG is excreted in urine and therefore it physiologically accumulates in the bladder, thus eventually masking the uptake of any superficial wall lesions and/or of the adjacent lymph nodes [ 43 ].…”
Section: 18 F-fdg Pet/ct For Preoperative Lymph Node Staging Of Mibcmentioning
confidence: 99%
“…Although, only one not updated meta-analysis showed a pooled sensitivity of 0.82 and specificity of 0.89 for metastatic lesion detection [38]. 18 F-FDG PET/CT is the most common molecular imaging technique for preoperative staging of various malignancies, due to the higher metabolic rate of cancerous cells com-pared to normal ones [39][40][41][42], however, as a glucose analog, 18 F-FDG is excreted in urine and therefore it physiologically accumulates in the bladder, thus eventually masking the uptake of any superficial wall lesions and/or of the adjacent lymph nodes [43]. Intense glucose metabolism in the primary tumor higher than FDG urinary excretion is present (A).…”
Section: F-fdg Pet/ct For Preoperative Lymph Node Staging Of Mibcmentioning
confidence: 99%